2018
DOI: 10.1037/ser0000177
|View full text |Cite
|
Sign up to set email alerts
|

Promising practices in vocational services for the community reintegration of returning veterans: The individual placement and support model and beyond.

Abstract: Supporting returning veterans' job-seeking, hiring, and retention issues has become an essential goal for effective community reintegration. Given both the particular strengths and challenges associated with veterans transitioning from military to civilian life, multiple models for supported employment have become integrated into Veterans Affairs health care facilities across the nation. In this article, we review the state of vocational rehabilitation for veterans, with a particular focus on individual placem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 56 publications
(65 reference statements)
0
6
0
Order By: Relevance
“…Work with veterans transitioning from the military to civilian life has suggested that IPS–SE could be modified including contingency management to decrease substance use, motivational interviewing to sustain motivation, and self-employment to avoid stigma (Wewiorski et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Work with veterans transitioning from the military to civilian life has suggested that IPS–SE could be modified including contingency management to decrease substance use, motivational interviewing to sustain motivation, and self-employment to avoid stigma (Wewiorski et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…• Comparisons between only members of the two groups who had found employment showed fewer differences between groups. illness (6), spinal cord injuries (7), posttraumatic stress disorder (PTSD) (8), and substance use disorders (9), as well as returning veterans (10). More recently, the number of hybrid or enhanced programs that combine supported employment with another standardized vocational program (11,12) or other therapeutic modalities (13) has increased.…”
Section: Ips-se Uses and Applicationmentioning
confidence: 99%
“…Reintegration for military personnel was further described as a dynamic process where individuals sought to resume association in social roles as civilians (Elnitsky & Kilmer, 2017). Desired community reintegration is dependent upon multidimensional support systems, including communal support, self-motivation, and social networks, for individuals transitioning from military to civilian life (Wewiorski et al, 2018). According to the Department of Defense (DoD) Dictionary of Military and Associated Terms ("Reintegration," n.d.-a.…”
Section: Reintegration Across Disciplinesmentioning
confidence: 99%